2010
DOI: 10.1016/j.ijheatmasstransfer.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Transient model for coupled heat, air and moisture transfer through multilayered porous media

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 9 publications
0
101
0
4
Order By: Relevance
“…COMSOL Multiphysics is based on finite-element resolution technique and provides an equation-based modeling module that allows users to encode their own PDEs equations. The latter is referred as "PDE interfaces module" (Tariku et al, 2010b). The two conservation equations were thus encoded in the following general form:…”
Section: Numerical Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…COMSOL Multiphysics is based on finite-element resolution technique and provides an equation-based modeling module that allows users to encode their own PDEs equations. The latter is referred as "PDE interfaces module" (Tariku et al, 2010b). The two conservation equations were thus encoded in the following general form:…”
Section: Numerical Resolutionmentioning
confidence: 99%
“…In the Matlab/Simulink popular environment, COMSOL Multiphysics (formerly FemLab) seems to be particularly interesting to manage the multidimensional PDE-based BEHAM problems (Tariku et al, 2010b;van Schijndel, 2009). It offers evident advantages in terms of modularity, transparency and ease of use.…”
Section: Introductionmentioning
confidence: 99%
“…A brief description of the transient building envelope model is presented, a detailed description of which are given in Tariku et al [16] and Tariku [17]. The model has the capability of handling the non-linear and coupled HAM transfer through multilayered porous media by taking into account the non-linear hygrothermal properties of materials, moisture transfer by vapor diffusion, capillary liquid water transport and convective heat and moisture transfers.…”
Section: Building Envelope Modelmentioning
confidence: 99%
“…The model can be used to simultaneously assess building enclosure durability, indoor conditions, occupant comfort, and also the energy efficiency of a building with the objective of attaining efficient building design. The development and benchmarking of a building envelop model, which is an essential building block to the holistic HAM model described in this paper, is presented in Tariku et al [16] and Tariku [17].…”
Section: Introductionmentioning
confidence: 99%
“…Janssen et al (2007) found that the common temporal discretisation of nonlinear equations may yield conservation errors, which can be solved by starting from the mixed transfer equation form. It should be noted that the three transport phenomena (HAM) were coupled and solved simultaneously for temperature, relative humidity and pressure considered as driving potentials by Tariku et al (2010). They leaned on the so called HAMFIT method which requires less time of implementation and provides a high degree of transparency and flexibility of modeling the coupled PDEs.…”
Section: Introductionmentioning
confidence: 99%